Learning Model of Basketball Dribbling Skills for Grades of 4-6 Elementary School - Giantana, Giantana; Widiastuti, Widiastuti; Yasep Setiakarnawijaya; Oman Unju Subandi; Rizki Ronaldo (UNIB Press, 2024)
This research was motivated by the low level of student activity in carrying out basketball dribbling movements during basketball learning. The aim of this research is to produce a product and determine the effectiveness of the basketball dribbling learning model for grades 4-6 of elementary school. research method with research and development of the ADDIE model. This research was conducted at SDN Duren Sawit 18 East Jakarta with research subjects being 60 students in grades 4 - 6 of elementary school, in March - June 2024. The results of this research are test results obtained before and after being given treatment with the basketball dribbling skills learning model. grade 4-6 elementary school, in the Paired T test the mean value = -13.267 shows the difference between the pre-test and post-test, with the t-count = -15.725, and p-value = 0.000 < 0.05 which shows that there was a significant difference between before and after the treatment model for learning basketball dribbling skills was given to students in grades 4-6 of elementary school. Thus, it can be concluded that the model for learning basketball dribbling skills is effective and can be applied in learning basketball dribbling for grades 4-6 of elementary school.